The role of interactive teaching methods in the formation of students’ professional competence - Nikolaevna, Kalinina Olga; Dolievna, Shakarova Feruza; Isanbayevna, Yadgarova Guzal (Linguistics and Culture Review, 2021)
This article is devoted to the topical topic of the application of interactive methods. Interactive teaching methods provide the solution to educational problems in various aspects. The interest in interactive methods is caused by the need to improve the modern system. The possession of interactive learning technology and its use in the educational process, including in Russian language lessons, will undoubtedly contribute to the development of students ’ qualities that correspond to the processes taking place in life today. The paper also presents the technologies of conducting Russian language lessons using interactive methods and their significance.